If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + -2x = -20 Solving 6 + -2x = -20 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + -2x = -20 + -6 Combine like terms: 6 + -6 = 0 0 + -2x = -20 + -6 -2x = -20 + -6 Combine like terms: -20 + -6 = -26 -2x = -26 Divide each side by '-2'. x = 13 Simplifying x = 13
| 15p+19.96=-14.08+11.3p | | 2(3r-7)-(2+r)= | | -11.4u-3.54+19.2u=8.34+8.9u | | -5.6k-16.61=-4.5k | | -13.03+5.1m=12.3m+10.01 | | -12.2w+16.74=-13.6w-7.2 | | 11.5d=-7.56+10.3d | | -6.5u+18.93=1.18-12.8u-8.08 | | -8.53-5+19.5z=18.1z-19.97 | | 7.82-1.5g=11.8g-16.12 | | -8.53-5+19.5z=18.1-19.97 | | -5s+16+12=-17-10s | | -4b+20=-18-b-19 | | -10j=19-11j | | 5n-6=6n+11 | | 2(22-8)=22+6 | | (z^(-1/2)z^(5/2))/(z^(1/3)) | | 10+6-3r=-10+10r | | 12(12k+11)=12(12k+12) | | 6x-35=71 | | 2(y-8)=y+6 | | 2.5=ln(7/x) | | 7=ln(2.5/x) | | 18y^2-37y-20=0 | | 2+.08x=.2x+8 | | Z2/6-7z/2-12=0 | | 6x^2+43x-15=0 | | 6/7z=3 | | 25a^2+25ac-14c^2=0 | | -6.1c=-24.4 | | 3(a+m)+2(b+n)-3a-2b=0 | | 3x-1=6T+2 |